Sexual exploitation by UN peacekeepers: the 'survival sex' gap in international human rights law. Issue 9 (22nd November 2017) - Mudgway, Cassandra
ABSTRACT: Allegations of sexual exploitation and abuse against United Nations peacekeepers over the past decade prompted a zero-tolerance policy response. Despite the many reforms to date, it is the troop-contributing countries which have exclusive criminal jurisdiction over their military contingent members and the current framework has been criticised for failing to ensure accountability of offenders. This article focuses on a particular form of sexual exploitation known as 'survival sex'; where sex is exchanged for aid or assistance which is already owed to the local population. In an effort to consider ways to improve individual accountability of perpetrators of survival sex, this article will explore three arguments; first, that survival sex should be considered violence against women under international human rights law and, second, that state obligations to respond to survival sex do not currently exist. Third, the question of whether the Committee on the Elimination of Discrimination against Women should consider filling the 'survival sex' gap will be discussed.